Optimization of Monascus purpureus for Natural Food Pigments Production on Potato Wastes and Their Application in Ice Lolly - Abdel-Raheam, Hossam E. F.; Alrumman, Sulaiman A.; Gadow, Samir I.; El-Sayed, Mohamed H.; Hikal, Dalia M.; Hesham, Abd El-Latif; Ali, Maysa M. A. (Frontiers in Microbiology, 2022)
During potato chip manufacturing, a large amount of wastewater and potato powder wastes are produced. The wastewater obtained at washing after peeling and cutting into slices was analyzed and a large quantity of organic compounds and minerals such as starch (1.69%), protein (1.5%), total carbohydrate (4.94%), reducing sugar (0.01%), Ash (0.14%), Crude Fat (0.11%), Ca (280mg/L), Mg (245mg/L), Fe (45.5mg/L) and Zn (6.5mg/L) were recorded, the reason for what these wastes could be considered valuable by-products if used as fermentation medium to increase the value of the subsequent products and to exceed the cost of reprocessing. in this study, we used wastewater and potato powder wastes as a growth medium for pigment and biomass production by Monascus purpureus (Went NRRL 1992). The response surface methodology was used to optimize of total pigment production and fungal biomass. The influence of potato powder waste concentration, fermentation period, and peptone concentration on total pigment and biomass production was investigated using the Box-Behnken Design method with 3-factors and 3-levels. The best conditions were obtained by statistical regression analysis and surface plots. The optimal production parameters for maximum total pigment concentration were potato powder waste concentration 7.81%, Fermentation period 12.82 day and peptone concentration 2.87%. The amount of total pigment produced was 29.86 AU/ml. The pigments produced were used as coloring agents for ice lolly. The present study has revealed that the ice lolly preparations supplemented with these pigments received high acceptability. Finally, we recommend using wastewater and potato powder wastes for pigment and biomass production, which could reduce the cost of the pigment production process on an industrial scale in the future.